Pengaruh Menonton Video tentang ‘Corona’ dari Bintang Emon terhadap Perilaku Social Distancing Mahasiswa FPSB UII - Rachmat Arya Prayuda; Puji Hariyanti (Program Studi Ilmu Komunikasi UII, 2021)
Bintang Emon uploaded a video containing complaints and an invitation to netizens to fight Corona on Twitter and Instagram. The video got quite a lot of attention from netizens. This study aims to determine the effect of videos about Corona from Bintang Emon on the social distancing behavior of students of the Faculty of Psychology and Socio-Cultural Sciences, Islamic University of Indonesia. This research is quantitative research with explanative type. This study shows that Bintang Emon's video has a positive and significant influence on the social distancing behavior of students of the Faculty of Psychology and Socio-Cultural Sciences, Islamic University of Indonesia. In the regression test, the results obtained a significance value of 0.02, which means > 0.05 and the t-count value of 3.144 > from the t-table which is worth 1.988. These results show that there is an influence given by the variable watching videos about Corona' from Bintang Emon on the social distancing behavior of FPSB UII students.Keywords: Corona, Effect, Social Media, Social Distancing.